2008
DOI: 10.1039/b810040c
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of the ground-state electronic structure of FMN by the conserved cysteine in phototropin LOV2 domains

Abstract: In LOV2, the blue-light sensitive domain of phototropin, the primary photophysical event involves intersystem crossing (ISC) from the singlet-excited state to the triplet state. The ISC rate is enhanced in LOV2 as compared to flavin mononucleotide (FMN) in solution, which likely results from a heavy-atom effect of a nearby conserved cysteine, C450. Here, we applied fluorescence line narrowing (FLN), resonance Raman (RR) and Fourier-transform infrared (FTIR) spectroscopy to investigate the electronic structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 65 publications
4
38
0
Order By: Relevance
“…Moreover, they proposed that it increases the intersystem crossing (ISC) rate by rapid generation of the reactive FMN triplet state, leading to a shortening of the FMN singlet excitedstate lifetime. These conclusions are consistent with several experimental studies, which state that the presence of the reactive cysteine at about 4 Å of the FMN [12,68,69] is responsible for a shortening of the singlet excited state lifetime and increase of the ISC rate by a factor of 2-3 as compared to FMN in solution [63,70] or cysteine-less mutants [71,72]. In this context, it is worth pointing out that in LOV domains an efficient ISC rate is crucial.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, they proposed that it increases the intersystem crossing (ISC) rate by rapid generation of the reactive FMN triplet state, leading to a shortening of the FMN singlet excitedstate lifetime. These conclusions are consistent with several experimental studies, which state that the presence of the reactive cysteine at about 4 Å of the FMN [12,68,69] is responsible for a shortening of the singlet excited state lifetime and increase of the ISC rate by a factor of 2-3 as compared to FMN in solution [63,70] or cysteine-less mutants [71,72]. In this context, it is worth pointing out that in LOV domains an efficient ISC rate is crucial.…”
Section: Resultssupporting
confidence: 91%
“…2S of the "Electronic supplementary material". They concluded this by comparing vibrational spectra from fluorescence line narrowing experiments of the wild-type LOV2 species AsLOV2 and Phy3LOV2 with a cysteine-less mutant AsLOV2-C450A [63]. They found that the mutant shows small but significant frequency shifts of the FMN ring vibrations as well as of the C2=O mode with respect to the wild-type species, similar to those found in FMN model systems with an electron-donating group substituted at the C8 position of the FMN.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Met-to-aliphatic side chain substitutions at analogous positions in flavodoxins affect the stability of reduced flavin species28. In addition, the presence of sulphur atoms in LOV domain active sites has been shown to impart quinoid character to the flavin18,29. Thus, substitutions of Met135 and Met165 in VVD should alter the electronics of the flavin ring and affect adduct stability.…”
Section: Resultsmentioning
confidence: 99%
“…20 The level of LOV-independent splicing, and the effect of blue light on the splicing of Npu inteins was measured using a C450S mutant of LOV2 that has previously been shown to be locked in its dark state even in the presence of blue light. 23 We observed no difference in spliced extein levels in samples incubated in the dark or in the presence of blue light ( Figure 2C), indicating that a functional LOV2 domain is required for the regulation InN-LOV-∆6InC splicing with blue light. Interestingly, incorporation of LOV C450S into the original Kan RInN-LOV-InC complex had no affect on the relative levels of spliced extein (Supplementary Figure 7), further indicating that the high affinity of the Npu split-intein fragments overrides any conformational inhibition of splicing when LOV is in its dark state.…”
Section: Introductionmentioning
confidence: 83%